2017
DOI: 10.1093/molbev/msx243
|View full text |Cite
|
Sign up to set email alerts
|

Diminishing Returns on Intragenic Repeat Number Expansion in the Production of Signaling Peptides

Abstract: Signaling peptides enable communication between cells, both within and between individuals, and are therefore key to the control of complex physiological and behavioral responses. Since their small sizes prevent direct transmission to secretory pathways, these peptides are often produced as part of a larger polyprotein comprising precursors for multiple related or identical peptides; the physiological and behavioral consequences of this unusual gene structure are not understood. Here, we show that the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…pombe strains, the number of P-factor–encoding repeats in the map2 gene varied from four to eight (Fig 2A). Variations in repeat number in the Saccharomyces genus have previously been reported [37,38]. For example, decreasing numbers of repeats in Mfα1, a structural gene for α-factor pheromone, results in a stepwise decrease in α-factor production in S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pombe strains, the number of P-factor–encoding repeats in the map2 gene varied from four to eight (Fig 2A). Variations in repeat number in the Saccharomyces genus have previously been reported [37,38]. For example, decreasing numbers of repeats in Mfα1, a structural gene for α-factor pheromone, results in a stepwise decrease in α-factor production in S .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the product of the map2 gene might need to have sufficient length for processing by the biosynthetic pathway. Although a higher repeat number in the map2 gene might result in increased P-factor production, further increases in repeat number do not necessarily lead to greater pheromone production because Rogers and colleagues [38] also showed that an 8-repeat strain is less favorable than a 6-repeat strain for mating choice in S . cerevisiae , probably due to reduced pheromone production caused by a decrease in the rate of translation.…”
Section: Discussionmentioning
confidence: 99%
“…In the special case of no manipulation or suppression, equation 1 simplifies to the classic tragedy of the commons model (Frank 1994(Frank , 1996(Frank , 1998Dionisio & Gordo 2006;Frank 2010a, b). We allow the effects of manipulation and suppression to be nonlinear by the shape parameters, 𝑎 and 𝑏. Nonlinearities can arise for a number of reasons, such as mechanisms of molecular diffusion, or interference between the behaviour of different individuals (Müller et al 2006;Wiley 2013;Rogers et al 2017). The parameter 𝑎 determines whether the benefit from increased investment into manipulation is decelerating (𝑎 < 1), linear (𝑎 = 1) or accelerating (𝑎 > 1).…”
Section: Model Designmentioning
confidence: 99%
“…Nonlinearities can arise for a number of reasons, such as mechanisms of molecular diffusion, or interference between the behaviour of different individuals (Müller et al . 2006; Wiley 2013; Rogers et al . 2017).…”
Section: Manipulative Cheating and Its Suppressionmentioning
confidence: 99%
“…We and others have proposed that variation in repetitive regions is an important driver of protein diversification (Fuchs, 2013, Gemayel, Yang et al, 2017, Morrill et al, 2016, Rogers, McConnell et al, 2017, Verstrepen, Jansen et al, 2005, Zhao, Strope et al, 2014. However, it is also possible that some or many of these repeats have randomly risen within the genome and thus are unlikely to contribute to protein function.…”
Section: Variable and Repetitive Idrs Are Conserved Across Saccharomymentioning
confidence: 99%